Estudo de catalisadores de NiSn/γ-Al2O3 para produção de hidrogênio através da reforma em fase aquosa do glicerol - Xavier, Ivan Pedro Arêdes Sousa (2023)
The search for renewable and cleaner sources of energy, aiming to reduce the consumption of fossil fuels, and consequently to reduce greenhouse gas emissions, to suppress the global energy demand, mainly from the transport industry, has stimulated many studiesIn this scenario, hydrogen (H2) has been increasing prominence, whether for its direct application as an energy source or being part of innovative biofuel production systems from more renewable sources. Due to these circumstances, the aqueous phase reforming reaction (APR) of glycerol has shown promise due to its high potential for H2 production and for its link to hydrocarbon production systems in the aviation biokerosene range. This work aims to evaluate the performance of NiSn/γ-Al2O3 catalysts (with a Ni/Sn molar ratio of 1, 5, and 10) during the glycerol APR reaction, aiming at the production of H2. The catalysts were synthesized by the wet impregnation method and then characterized using the techniques: N2 Physisorption, X-ray Fluorescence (XRF), X-ray Diffraction (XRD), Reduction with H2 at Programmed Temperature (TPR- H2), H2 Desorption at Programmed Temperature (TPD-H2) and Propylene Hydrogenation. After characterization, the catalytic test was performed with all the catalysts through glycerol APR reaction at 250°C and 50 bar pressure in a continuous system. Through the characterization data, it was observed a decrease in the surface area of the catalysts after impregnation with Sn and a decrease in the active metal (Ni0) area. The XRD showed a weak interaction between the active metal and the support, leading to the formation of stronger interactions between Ni and Sn, which favored the formation of Ni3Sn and Ni3Sn2 alloys. TPR-H2 demonstrated that the presence of Sn did not change the reduction profile of the catalysts but promoted a decrease in the degree of reduction. TPD-H2 showed that the presence of Sn possibly limited the different adsorption mechanisms, leading to more uniform active sites. Through the catalytic test, a very rapid deactivation of the catalyst was observed, within up to 14 hours, especially for catalysts that featured the Ni3Sn alloy, deactivating within 3 hours. The catalysts with Sn showed a gas selectivity of 100% to H2 and a high formation of hydroxyacetone in the liquid phase. The deactivation of the catalyst possibly occurred due to carbon deposit, due to the weak interaction between the active metal and the support, the increase in acidity of the catalytic site due to the presence of Sn, and a high formation of hydrocarbons in the liquid phase.